2010
DOI: 10.1590/s0102-695x2010000200021
|View full text |Cite
|
Sign up to set email alerts
|

O oleo essencial de Lippia gracilis Schauer, Verbenaceae, em ratos diabeticos

Abstract: RESUMO: "O oleo essencial de Lippia gracilis Schauer, Verbenaceae, em ratos diabeticos". O óleo essencial das folhas de Lippia gracilis Schauer, Verbenaceae, foi examinado por CG e CG-MS. Quinze constituintes foram identificados, onde o carvacrol, p-cimeno e o γ-terpineno foram as substâncias majoritárias. No estudo in vitro, a solução a 5% do óleo de L. gracilis Schauer apresentou atividade antibacteriana para Staphylococcus aureus isolado de úlcera infectada de paciente diabético. O estudo avaliou a atividad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…Therefore, in the dry season these constituents are present in higher concentrations. The chemical constituents carvacrol and p-cymene are described in several studies as major constituents; nevertheless, in this species, they were not identified or had low contents [29][30][31]. The chemical constituents in the three periods showed small variations in concentrations.…”
Section: Chemical Analysis Of Lippia Grata Essential Oilsmentioning
confidence: 78%
“…Therefore, in the dry season these constituents are present in higher concentrations. The chemical constituents carvacrol and p-cymene are described in several studies as major constituents; nevertheless, in this species, they were not identified or had low contents [29][30][31]. The chemical constituents in the three periods showed small variations in concentrations.…”
Section: Chemical Analysis Of Lippia Grata Essential Oilsmentioning
confidence: 78%
“…Em estudo realizado por Neto et al, (2010), visando as infecções por Staphylococcus aureus, foi verificada a sensibilidade por difusão em disco, determinando o diâmetro de zona de 26mm (OE a 5% v/v) e 25 mm (OE a 5% v/v). Além disso, foi realizado experimento em 28 ratos diabéticos que foram divididos em quatro grupos: 1 (controle negativo-branco); 2 (controle negativo-óleo); 3 (controle positivo); e 4 (teste), em que foi inoculado 0,05mL de DMSO a 2% (v/v) com 105 UFC/mL de S. aureus e, depois de 24 h, foi inoculado 0,05 mL de solução de Lippia gracilis (v/v) com DMSO a 2% (v/v).…”
Section: Atividade Antimicrobianaunclassified